2010
DOI: 10.1152/ajpendo.00437.2009
|View full text |Cite
|
Sign up to set email alerts
|

Protein restriction during pregnancy affects maternal liver lipid metabolism and fetal brain lipid composition in the rat

Abstract: Protein restriction during pregnancy affects maternal liver lipid metabolism and fetal brain lipid composition in the rat. Am J Physiol Endocrinol Metab 298: E270 -E277, 2010. First published November 17, 2009 doi:10.1152/ajpendo.00437.2009.-Suboptimal developmental environments program offspring to lifelong metabolic problems. The aim of this study was to determine the impact of protein restriction in pregnancy on maternal liver lipid metabolism at 19 days of gestation (dG) and its effect on fetal brain deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 42 publications
2
71
1
3
Order By: Relevance
“…There is also considerable variability in the length, degree and timing of nutritional restriction 151 between studies [79][80][81][82][83][84][85][86][87][88], with some studies restricting throughout gestation or the entire length of 152 pregnancy studied [79,82,86,89], whilst others may only restrict during part of gestation [80,83,153 84, 88], or extend maternal nutrient restriction into lactation [85,87]. The patterns of restriction in 154 these models also differ from that in human IUGR due to placental insufficiency, which 155 progressively worsens during pregnancy [ Figure 2,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is also considerable variability in the length, degree and timing of nutritional restriction 151 between studies [79][80][81][82][83][84][85][86][87][88], with some studies restricting throughout gestation or the entire length of 152 pregnancy studied [79,82,86,89], whilst others may only restrict during part of gestation [80,83,153 84, 88], or extend maternal nutrient restriction into lactation [85,87]. The patterns of restriction in 154 these models also differ from that in human IUGR due to placental insufficiency, which 155 progressively worsens during pregnancy [ Figure 2,14].…”
mentioning
confidence: 99%
“…Diagram does not show representative of the timing described in the literature: rat UPL [112,115] the variety of timing used in these studies they are not shown above. Fetal weight ↓13% [199] ↓5-35% [86,104,200] ↑7-25% [201] = [80] [82] ↓11% [82][128] ↓8-31% [112 , 202-204] = E19, ↓E21 [160] ↓22-63% [106, 119, 121, 142-144, 161, 162, 205-207] ↓20-36% [102,208,209] ↓20-42% [108,109,111] ↓15-43% [11,107,210,211] Placental weight ↓9.5-35% [104,200] = [86] ↑↓ during pregnancy [201] = [89] ↓size as pregnancy progresses [82] ↓20% [202] ↓21-40% [106, 142-144, 161, 206] = [102,208] ↓44% [212] ↓35% [109] ↓36-64% [11,107,132,210,211] Fetal brain size = [86] ↑12% [201] ↓E90, = E135 [82] =E16, E18 [128] ↓E20 …”
mentioning
confidence: 99%
“…Rats. [grupo-controle: 12,00 (9,(0)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)00) dias; POFG=9,50 (9,(0)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)00) dias] e queda livre [grupo-controle:18,00 (17,00); POFG=16,00 (13,(0)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)…”
Section: Resultsunclassified
“…According to Torres et al 10 , moderate protein restriction (10%) reduces the amount of Arachidonic Acid and Docosahexaenoic Acid (DHA) in the dam's liver, along with the enzymes that elongate and desaturate essential fatty acids, resulting in lower fat content in the fetal brain. Marin et al 33 then showed that these events are minimized when dietary fat consists of soybean oil, even if protein content is below 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that restriction of protein intake during pregnancy may have a negative effect on fetal brain development. This is thought to be due to changes in maternal metabolism of lipids, which are an essential component of cellular membranes 39 . Interestingly, the behavioural abnormalities seen in these protein restricted models do not manifest until early adulthood, including effects on brain-regulated activities such as decreased pre-pulse inhibition of the startle response and hyperlocomotion, which are traditionally used as a measure of schizophrenia-like behavior 40,41 .…”
Section: Behavioral and Psychological Problemsmentioning
confidence: 99%